Teachers’ Strategies and Challenges to Promote Students’ Active English Learning in SMK Muhammadiyah 1 Palu - Chairiyah, Wiwik; Usman, Sriati; Kamaruddin, Abdul (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
Student engagement has an important aspect in achieving excellent learning outcomes for learners and further improving their abilities. So teachers must have strategies to encourage student involvement. The aim of this research was to investigate the strategies the teachers use in activating students active learning in teaching and learning process and the challenges the teachers face in promoting students active learning. The researcher used qualitative research. The place of the research was in SMKS Muhammdiyah 1 Palu that located in Letjend Seoprapto. The Subject of the research were all English teachers at SMK Muhammadiyah 1 Palu that consist of four teachers. The data collection techniques that wil be used are: In depth Interview, Observation, and Documentation. The data will be analyzed in 3 steps, are Data reduction, data display, and conclusion. After conducting a research in SMK Muhammadiyah 1 Palu, it is found that in stimulating students’ active English learning, the teachers use six strategies; Questionning & discussion, visual based instruction, rolep lay, game, project based learning, and discovery based learning.From those six strategies the teachers used in the previous explanation, there are four strategies that are used dominantly; questioning & discussion, visual based instruction, project based learning, and discovery based learning.researcher proposes that future researchers interested in the same issue might do in-depth research on teacher ways to encourage students' active learning in English. For instance, the specific strategy that can stimulate the specific skill.